Prinsip Pembangunan Infrastruktur yang Berlandaskan HAM Terhadap Eksistensi Masyarakat Hukum Adat di Indonesia - Raden Muhammad Arvy Ilyasa (Faculty of Law, Universitas Pattimura, 2020)
Infrastructure development can simplify the flow of the economy and provide accessibility for the community to reach public facilities that have been provided. This study aims to examine the problem of infrastructure development in Indonesia, which often occurs in conflicts between indigenous peoples and the government regarding land for infrastructure development on the ulayat lands of indigenous peoples. The research method used normative research with an statute approach, conceptual approach and analyzed descriptively qualitatively. The results show that in infrastructure development in Indonesia, several aspects must be considered, such as the balance of development and the interests of the community, paying attention to aspects of human rights so that this does not happen. One suitable concept is Free Prior Informed and Consent (FPIC) as a form of recognition of the existence of indigenous peoples as the subject of development, not as objects of development.